2013
DOI: 10.1016/j.jconrel.2013.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and bioimaging studies of hybrid paclitaxel nanocrystals: Lessons learned of the EPR effect and image-guided drug delivery

Abstract: Paclitaxel (PTX) nanocrystals (200 nm) were produced by crystallization from solution. Antitumor efficacy and toxicity were examined through a survival study in a human HT-29 colon cancer xenograft murine model. The antitumor activity of the nanocrystal treatments was comparable with that by the conventional solubilization formulation (Taxol®), but yielded less toxicity as indicated by the result of survival study. Tritium-labeled PTX nanocrystals were further produced with a near infrared (NIR) fluorescent dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 47 publications
4
104
0
Order By: Relevance
“…The sequence of organ fluorescence intensity is Liver4Spleen4Lungs4Kidney 4Tumor4Heart. Similar type of tissue distribution was reported in the previous literature (Hollis et al, 2013;Liu et al, 2014). When ALNE was administered, the average radiance emitted by tumor was 3.04 times more than that of DLNE formulation.…”
Section: Resultssupporting
confidence: 85%
“…The sequence of organ fluorescence intensity is Liver4Spleen4Lungs4Kidney 4Tumor4Heart. Similar type of tissue distribution was reported in the previous literature (Hollis et al, 2013;Liu et al, 2014). When ALNE was administered, the average radiance emitted by tumor was 3.04 times more than that of DLNE formulation.…”
Section: Resultssupporting
confidence: 85%
“…Our in vivo experiments have demonstrated that nanocrystal formulations of chemotherapeutic agents are capable of eliciting similar and better anticancer efficacy-compared with solubilized or encapsulated delivery systems-but exhibiting much reduced side effects (1,2). This may be contributed by the absence of helper chemicals that are used in the conventional formulations for solubilizing and/or encapsulating poorly soluble drugs (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 92%
“…Cellular Uptake Imaging of Nanocrystals KB cells were seeded in confocal petri dishes at a density of 2×10 5 cells/well and cultured for 24 h. After adhering to dish walls, the KB cells were incubated in FA-deficient RPMI 1640 medium with 100 μg/mL SRB-PTX-NCs at different durations (15, 30 min, 1, 2, and 3 h) or incubated for 3 h with the concentration of the nanocrystals varied (1,5,25, and 100 μg/mL). Additionally, the KB cells were incubated for 3 h in FA-deficient RPMI1640 medium with 100 μg/mL bare or surface-modified SRB-PTX-NCs (PEG-Dp-SRB-PTX-NCs, FA-PEG-Dp-SRB-PTX-NCs, PEG-SRB-PTX-NCs, FA-PEG-SRB-PTX-NCs, F 127 -SRB-PTX-NCs, and F 68 -SRB-PTX-NCs).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that the micelles were sequestered by the macrophage phagocytic system (MPS) within few minutes of intravenous administration. The liver may temporarily act as a depot site of the drug and release the drug back into the systemic circulation, which could prolong the retention time of PTX (Hollis et al, 2013). Specially, for cancer therapy, it is important to reduce drug accumulation in the key organs, such as the heart and kidney, to avoid or minimize systemic side effects.…”
Section: Tissue Distribution In Micementioning
confidence: 99%